THE CORRELATION BETWEEN LEARNING STRATEGIES AND STUDENTS ACHIEVEMENT IN SPEAKING FOR ENGLISH SPECIFIC PURPOSE (ESP) IN ADMINISTRATION FACULTY OF UNISMA. - Muhamad Saiful; Mutmainnah Mustofa; Kurniasih kurniasih (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
The aim of this study is to find out the most strategies used by ESP students in learning speaking and to find out whether or not a correlation between learning strategies and achievement in speaking. The subject of this study was 30 students of business administration of the seventh semester. The data were collected using a questionnaire and score of speaking. The result of this research showed that the finding that correlation between learning strategies and achievement in speaking is positive result means that there is correlation between learning strategies and students achievement in speaking skill but the level of correlation is small. The level sig. (2 tailed) was greater than the level of significant (0.140 < 0.05), then H0 was accepted H1 was rejected. It can be said that not all students of business administration use strategies in learning English especially speaking skill. Meaning that the students who use strategies have good score and students who lowest score also use strategies but the strategies is not suitable with them. These finding imply that resource-based strategy is the most influential strategy in speaking class to help students, particularly for ESP students to overcome their problem in speaking performance. The students suggested applying the strategies provided to overcome their difficulties. However, this research was expected to be developed by the future researchers who had the same interest.